Automated reasoning : 10th International Joint Conference, IJCAR 2020, Paris, France, July 1-4, 2020, Proceedings.: 10th International Joint Conference, IJCAR 2020, Paris, France, July 1-4, 2020, Proceedings. Part II (2020) - Unknown
No abstract available